2017
DOI: 10.1038/ncomms15721
|View full text |Cite
|
Sign up to set email alerts
|

Towards colloidal spintronics through Rashba spin-orbit interaction in lead sulphide nanosheets

Abstract: Employing the spin degree of freedom of charge carriers offers the possibility to extend the functionality of conventional electronic devices, while colloidal chemistry can be used to synthesize inexpensive and tunable nanomaterials. Here, in order to benefit from both concepts, we investigate Rashba spin–orbit interaction in colloidal lead sulphide nanosheets by electrical measurements on the circular photo-galvanic effect. Lead sulphide nanosheets possess rock salt crystal structure, which is centrosymmetric… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 43 publications
(131 reference statements)
0
26
0
1
Order By: Relevance
“…Early characterization of PbS nanosheets showed that they exhibit p‐type behavior when they are probed as field‐effect transistors . In order to effectively implement these nanosheets into applications like transistors, solar cells, photodetectors, and spintronic devices (based on the Rashba spin–orbit coupling), it is crucial to improve the p‐type behavior and also to develop the possibility to switch the behavior to n‐type . Doping colloidal nanomaterials, in contrast to conventional semiconductors, is complex since it depends on several parameters, such as the stoichiometry of the crystals, traps on the surface, passivating ligands and impurities .…”
Section: Introductionmentioning
confidence: 99%
“…Early characterization of PbS nanosheets showed that they exhibit p‐type behavior when they are probed as field‐effect transistors . In order to effectively implement these nanosheets into applications like transistors, solar cells, photodetectors, and spintronic devices (based on the Rashba spin–orbit coupling), it is crucial to improve the p‐type behavior and also to develop the possibility to switch the behavior to n‐type . Doping colloidal nanomaterials, in contrast to conventional semiconductors, is complex since it depends on several parameters, such as the stoichiometry of the crystals, traps on the surface, passivating ligands and impurities .…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, it has been shown that the size reduction of different materials has led to the emergence of many novel properties due to the employment of quantum confinement. [ 1 ] For instance, the realization of spin‐dependent phenomena, [ 2,3 ] unconventional superconductivity regimes, [ 4 ] and topological surface states [ 5 ] attracted considerable attention. Nevertheless, there is still room to tune the shape and size of nanomaterials, which might further modify their properties or even fundamentally change their character.…”
Section: Introductionmentioning
confidence: 99%
“…[ 6,8 ] One example for the successful implementation of this approach is the synthesis of lead sulfide, which has been produced with a broad spectrum of shapes, sizes, and properties. [ 10–12 ] This material has been already used for many applications such as photodetectors, [ 13 ] field‐effect transistors, [ 14 ] spintronic components, [ 2 ] and solar cells. [ 15,16 ] Regarding all of these applications, a certain statement is valid: PbS exhibits semiconducting properties, which is not a surprising fact considering the electronic structure of this material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,40 Multi-exciton generation and tunable electrical features by halide ion doping were studied to improve nanosheet based devices as possible components in semiconductor industries. [41][42][43] Here, we present the synthesis of PbS nanoframes as intermediate nanostructures on the pathway to PbS nanorings. The synthesis starts with the formation of initial PbS nanosheets, which undergo a thermally induced ripening process in the presence of halide ions first forming nanoframes and later nanorings via additional halide ion etching.…”
Section: Introductionmentioning
confidence: 99%